Toxicity and Antioxidant Activity Test of Rambutan Seeds (Nephelium lappaceum L.) - Arum, Alvionita Puspa; Rahmadani, Agung; Rijai, Laode; Farah, Harra Ismi (Universitas Pendidikan Mandalika, 2025)
Rambutan (Nephelium lappaceum L.) seeds have long been utilized in traditional medicine due to their potential therapeutic properties. This study aimed to determine the secondary metabolite profile, toxicity, and antioxidant activity of the methanolic extract and ethyl acetate fraction of rambutan seeds to strengthen their potential application in traditional medicine. The powdered of rambutan seed was extracted with a maceration technique using methanol, followed by fractionation using n-hexane and ethyl acetate. The methanol extract and ethyl acetate fraction were tested for toxicity using the Brine Shrimp Lethality Test (BSLT) and for antioxidant activity using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. Phytochemical screening was performed using standard qualitative method to identify secondary metabolites, which confirmed the presence of phenols, tannins, and flavonoids in both samples. Toxicity testing indicated LC₅₀ values of 688.86 ppm for the methanol extract and 825.68 ppm for the ethyl acetate fraction. Antioxidant activity assessment revealed IC₅₀ values of 328.61 ppm for the methanol extract and the higher activity for ethyl acetate fraction of 32.78 ppm. These results indicate that the ethyl acetate fraction of rambutan seeds may serve as a promising natural source of antioxidants for therapeutic development.